Perioperative Carbon Dioxide Narcosis during ERCP: Report of Two Cases - Aditya N Shukla; Surendra Kumar (Journal of Clinical and Diagnostic Research, 2019)
Endoscopic Retrograde Cholangiopancreatography (ERCP) is a common diagnostic and therapeutic gastrointestinal intervention. It is gaining prominence and use because of low morbidity associated with it compared to surgical procedure. ERCP is usually conducted outside operating suite, with compromised position under deep sedation or General Anaesthesia (GA) without control of airway. We report development of CO2 narcosis in two patients who underwent ERCP under general anaesthesia, for removal of biliary stone and biliary stenting. We also reviewed the available literature on administration of anaesthesia and monitoring for ERCP.